The LOXL1 antisense RNA 1 (LOXL1-AS1)/microRNA-423-5p (miR-423-5p)/ectodermal-neural cortex 1 (ENC1) axis promotes cervical cancer through the mitogen-activated protein kinase (MEK)/extracellular signal-regulated kinase (ERK) pathway. Issue 2 (1st February 2022) - Zhang, Ping; Zhao, Fang; Jia, Ke; Liu, Xiaoli
ABSTRACT: As the fourth commonest malignancy among females worldwide, cervical cancer (CC) poses a huge challenge to human health. The pivotal regulatory roles of lncRNAs in cancers have been highlighted. LOXL1 antisense RNA 1 (LOXL1-AS1) has been reported to play a key role in cervical squamous cell carcinoma and other various cancers. Thus, we investigated the roles and mechanisms of lncRNA LOXL1-AS1 in CC. The in vivo experiments demonstrated that LOXL1-AS1 downregulation inhibited tumor growth and metastasis and proliferation of CC cells. The results of RT-qPCR demonstrated that LOXL1-AS1 and ectodermal-neural cortex 1 (ENC1) expression levels were upregulated in CC cells and tissues, while microRNA-423-5p (miR-423-5p) level was downregulated. As subcellular fractionation assays, RNA pull down assays and luciferase reporter assays revealed, LOXL1-AS1 bound to miR-423-5p and miR-423-5p targeted ENC1. 3-(4, 5-Dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assays, wound healing and colony formation assays demonstrated that miR-423-5p upregulation and LOXL1-AS1 downregulation inhibited CC cell proliferation and migration, while ENC1 upregulation attenuated the inhibitory effects of miR-423-5p upregulation on the malignant phenotypes of CC cells. Western blotting was conducted to measure protein levels and the results showed that ENC1 knockdown inhibited the activation of ERK/MEK pathway. In summary, the LOXL1-AS1/miR-423-5p/ENC1 axis accelerates CC development through the MEK/ERK pathway.